ANGLİKAN KİLİSESİ’NİN OSMANLI’DAKİ SANCAKTARI: CHURCH MISSIONARY SOCIETY: HEDEFLERİ, MİSYONERLİK TANIMI VE MOTİVASYON UNSURLARI- III - (:unkn) unknown (My University, 2014)
On sekizinci yüzyıl sonunda gerçekleşen Sanayi Devrimi, İngiltere’nin teknolojik, askeri ve siyasi üstünlüğüyle neticelenen büyük ölçekli bir dönüşümün habercisi olmakla kalmamış, aynı zamanda Protestan misyoner teşkilatları açısından da altın bir çağın yaşanması için gerekli altyapıyı hazırlamıştır. London Missionary Society (1795), British and Foreign Bible Society (1804), London Jews’ Society (1809) gibi cemiyetlerin yanısıra Church Missionary Society (1799) hem Anglo-Sakson hem Amerikalı türdeşlerini geride bırakan bütçesinin kazandırdığı güçle, Afrika’dan Okyanusya’ya kadar yayılan farklı coğrafyalarda Hristiyanlaştırma hedefini gerçekleştirmek üzere özel olarak yetiştirilip desteklenmiş misyonerlerini görevlendirmiş- tir. XIX. yüzyıl boyunca her ne kadar ülkesine, toplumuna ve zamanına göre değişen yöntem ve yoğunluk boyutuyla hedeflerine ulaşmaya çalışmışlarsa da, misyon stratejilerinin temelinde “Batı’nın imkânlarından istifade etmek” ve “Batılı medeniyetler seviyesine ulaşmak” argümanları büyük önem taşımıştır. Bu bağlamda, çalışmada; XIX. yüzyılda dünyanın en büyük Protestan teşkilatlarından olan Church Missionary Society’nin misyon anlayışını ve misyonerlik faaliyetlerini dayandırdıkları temel postulatlar ile bunların başlangıç, gelişim ve tutunma stratejileri, modern dünyanın sekü- ler yönde değişimine paralel olarak din ve medeniyet arasında kurdukları rabıtanın anlam ve önemi incelenmeye çalışılmıştır.

Having come to the fore at the end of the eighteenth century, Industrial Revolution not only was the precursor of a grand-scaled transformation resulted in the technological, military, and political superiority of England, but also created the infrastructure of a golden era for the Protestant missionary organizations. Alongside such societies namely as London Missionary Society (1795), British and Foreign Bible Society (1804), London Jews’ Society (1809), Church Missionary Society (1799), with the power it gained thanks to its budget, which surpassed both its Anglo-Saxon and American congeners, commissioned its specially trained and supported missionaries throughout a wide geography, expanding from Africa to Oceania, for the sake of the purpose of Christianization. Despite having attempted to achieve their targets by means of methods and intensities, varying from each other as per country, society, and time, throughout the 19th Century, the mission strategies essentially proclaimed the arguments of “benefiting from the opportunities of the West”, and “reaching to the level of Western civilizations”. Within this context, what is intended in this study is to observe the basic postulates, on which Church Missionary Society, which was one of the world’s biggest Protestant organizations, grounded its sense of mission and its missionary activities, and the initiation, development, and adherence strategies thereof, as well as to observe the meaning and significance of the relation they constituted between religion and civilization in parallel with the secular direction of the change in the modern world.
The Bannerman Of Anglican Church in The Ottoman Empire: Church Missionary Society-Its Aims, Missionary Perception and Motivation Factors- III
Keywords: Din Bilimi